Cooperative catalysis by bovine serum albumin–iodine towards cascade oxidative coupling-C(sp2)–H sulfenylation of indoles/hydroxyaryls with thiophenols on water. Issue 25 (2nd June 2016) - Saima; Equbal, Danish; Lavekar, Aditya G.; Sinha, Arun K.
Abstract : Bovine serum albumin–iodine acts as a cooperative catalyst for C(sp 2 )–H sulfenylation of indoles and hydroxyaryls ( i.e. 2-naphthol/4-hydroxycoumarin) with diverse thiols (aryl/heteroaryl) using water under aerobic conditions. Abstract : Cooperative cascade catalysis by bovine serum albumin (BSA)–iodine allows for the first time the performance of C(sp 2 )–H sulfenylation of indole from readily available thiophenol (–SH bond) via in situ generation/cleavage of disulfide (S–S bond) in air under aqueous conditions, whereas BSA or I2 individually do not permit this two step sequence to occur in the same pot towards C–S bond formation. This green cooperative protocol is extendable to sulfenylation of hydroxyaryls ( i.e. 2-naphthol or 4-hydroxycoumarin) with diverse thiols (aryl/heteroaryl) without using any toxic metal catalysts, bases or oxidants, thus rendering the process environmentally and economically reliable. Further, the gram scale synthesis of a COX-2 inhibitor (3-(pyridin-2-ylthio)-1 H -indole), regioselectivity and recyclability (up to four cycles) are the additional merits of this cooperative cascade bio-chemocatalytic (BSA–I2 ) protocol. Moreover, HPLC and ESI-MS provide powerful insights into the mechanistic aspects of the above cascade sulfenylation reaction.